Ce que révèle l’exil politique sur les relations entre les États italiens - Christine Shaw (Laboratoire Italien)
The practice of political exile was particularly widespread in Renaissance Italy. The issues related to exiles were a major element of the official relationships between Italian states. The exiles themselves represented a significant part of the network of contacts –informal and dense– that would connect the populations of the various states with each other. The way governments treated exiles from other states was considered as a major hint on their true attitude towards the other governments. In order to control their exiles, States sought help and cooperation, however “host” governments would have often put forward the argument that it was preferable to treat the exiles in fair way not to incite them to commit acts of desperation. The treatment of and the attitude with the exiles are a sign of the strong interest of the Italian states for the domestic affairs of the other states. It also shows how important was for governments’ reputation, in their own states, the reputation they enjoyed in the other governments.